Neumann conditions for the higher order s-fractional Laplacian (−Δ)su with s>1. (April 2020) - Barrios, Begoña; Montoro, Luigi; Peral, Ireneo; Soria, Fernando
Abstract: In this paper we study a variational Neumann problem for the higher order fractional Laplacian ( − Δ ) s, s > 1 . In the process we introduce some nonlocal Neumann boundary conditions that appear in a natural way from a Gauss-like integration formula.